A (magyar) politikai diskurzus minősége - Csordás Noémi (2020)
The paper aims to clarify the meaning of political discourse in light of Michel Foucault’s, Paul Ricoeur’s and Teun A. Van Dijk’s works. According to them, discourse is the main component in one’s existence, something that none of us can escape. Discourse is a two-sided process, in which there has to be a speaker and a receiver. Political discourse is a phenomenon in which the speaker needs a political-institutional background, a political theme and has to appear as a politician. The research focuses on Viktor Orban’s political speeches from 2014 (his 2nd inauguration) to 2018 (parliamentary elections). We can divide this timeframe into two sections: June 2014 – February 2018, the „peaceful period” and February 2018 – April 2018, the campaign period. The goal of the research was to determine whether there was a difference in the quality of the political discourse in these two periods. In order to establish the quality of the discourse, we applied the Discourse Quality Index developed by Steenbergen and others. We supplemented the DQImethod with machine learning in order to make the coding process faster and more reliable. For this, we used Fournier-Tombs’ DelibAnalysis tool. Our model is still under development, our results will be published later.
Keywords: Bölcsészettudományok; Történettudomány és régészet